PROJETO E CONSTRUÇÃO DE UMA BANCADA PARA ENSAIO DE TRANSMISSÕES MECÂNICAS DO TIPO TREM DE ENGRENAGENS - Pereira, Jean C. B.; Padoin, Eduardo; Ritter, Douglas; Valdiero, Antonio C. (Salão do Conhecimento, 2013)
Resumo